PENYULUAN TENTANG PENGOBATAN ANTIKOLESTROL PADA AFRIKA (Gymnanthenemum Amygdalina Del.) DAN KELAPA SAWIT (Elaeis Guineensis Jacq.) DIPUSKESMAS NAMORAMBE - Wahyudi Wahyudi; Sulasmi Sulasmi; Sri Sudewi Pratiwi Sitio (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Use of therapeutic plants by individuals of Indonesia up to this point has been broadly used to beat different sicknesses including avoidance, therapy and mainte-nance of wellbeing. One of the plants that can be utilized to treat hypercholeeroladalah African leaves that contain a gathering of saponin compounds, lactone seskuterpenes, flavonoids, glycosides, tannins and triterpenoids/steroids Riansari (2008). The Center for Public Health (Puskesmas) is a medical care office that sorts out general wellbeing endeavors and top notch individual wellbeing endeavors, focusing on promotive and pre-ventive endeavors, to accomplish the most significant level of general wellbeing in their workspace. Puskesmas has the assignment of carrying out wellbeing strategy to accomplish wellbeing create ment objectives in its workspace to help the acknowledgment of sound subdis-tricts (Permenkes, 2014).Cholesterol is one of the components in forming fat. In fat there are various components such as triglycerides, phospholipids, free fatty acids, and cholesterol. In general, cholesterol serves to build the inner wall of the cell (cell membrane) in the body. Not only that, cholesterol also plays an important role in producing sex hormones, vitamin D, and plays an important role in carrying out nerve and brain functions (Mumpuni & wulan, 2011). Palm oil (Elaeis guineensis Jacq.) is one of the plants that has great potential in Indonesia. Oil palm plantations can improve welfare and social status so that it becomes a trend among the people of Indonesia.Palm oil (Elaeis guneensis Jacq.) industrial plants / plantations that become a source of state foreign exchange from the plantation sector. Palm oil plants are useful as producers of cooking oil, industrial oil, and fuel (Dianto et al. 2017).A medication that is frequently used to bring down cholesterol levels is simvastatin, this medication works by repressing the development of cholesterol by restraining the compound HMG CoA re-ductase. Be that as it may, long haul utilization of simvastatin might give some secondary effects, for example, hepatotoxic, discomfort, rabdomiolysis, myopathy, and so forth (Yuniarti, 2016)